Study on Deformation Behavior and Mechanical Properties of 42CrMo High-Strength Steel with Multi-Station Warm Upsetting - Zhiling Xiao; Hao Wang; Jinhua Liu; Junjie Jiang; Liming Yu; Yuhao Zhang (Metals, 2024)
In order to find out the deformation behavior and mechanical properties of 42CrMo steel under warm upsetting conditions, the Gleeble-3500 thermal simulation testing machine was used to carry out a warm upsetting physical simulation experiment on 42CrMo steel. By controlling deformation temperature, strain rate, and constant temperature deformation pass, the microstructure evolution rule under different warm upsetting conditions was analyzed, and its hardness value was measured. Then, the simulation experiment is carried out based on the Deform-3D finite element platform. The results show that, with the increase in deformation temperature, 42CrMo steel has a temperature rise softening effect, which significantly reduces the peak value of rheological stress. At 650 °C, the maximum peak value of rheological stress is only 45.3% of that of cold upsetting deformation at room temperature, and the stress-strain curve tends to be gentle at the plastic deformation stage, which is the most suitable temperature for warm upsetting deformation. The maximum peak flow stress of 42CrMo steel increases with the increase in strain rate, but the number of deformation channels has little influence on the stress-strain curve. The warm, upsetting deformation can refine the internal grain structure significantly, and the grain refinement mechanism is mechanical crushing. When the temperature is slightly higher, the broken grain will recover, and the grain size will grow. During the process of warm upsetting, the strain rate has a great influence on the microhardness of the sample. The deformation pass has little influence on the hardness, and the hardness increases slightly with the increase in the deformation pass. Through the Deform-3D simulation, the correlation coefficient R and the average absolute relative error (AARE) between the simulation value and the experimental value were calculated, and the correlation coefficient R-value was 0.9948, and the average absolute relative error (AARE) was 2.05%, indicating that the simulation can accurately reflect the relationship between displacement and applied load.